1991
DOI: 10.13031/2013.31828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Moisture Stress Levels on Corn Growth in Field Lysimeters

Abstract: Experiments were conducted in field lysimeters to investigate the effects of high water table positions (created by subirrigation practice) on com growth. Various plant growth parameters (plant dry matter, canopy height, and yield) were measured before, during, and after the excessively wet periods. Two regression models were developed to characterize corn yield production as a function of durations of excessively wet periods and water-table positions. Results indicated that subirrigation practices can improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Literature studies have shown a 7-27% maize yield increase with decreasing water table depth from 0.5 m to 1.5 m in Iowa (Ahmad and Kanwar, 1991;Kalita and Kanwar, 1992;Helmers et al, 2012) and an optimum water table depth for maximizing maize production in other environments (Florio et al, 2014). In our study we did not find a significant correlation between water table depth and yield (P > 0.30; Fig.…”
Section: Predictability Of Root Growth and Water Table Effectscontrasting
confidence: 54%
“…Literature studies have shown a 7-27% maize yield increase with decreasing water table depth from 0.5 m to 1.5 m in Iowa (Ahmad and Kanwar, 1991;Kalita and Kanwar, 1992;Helmers et al, 2012) and an optimum water table depth for maximizing maize production in other environments (Florio et al, 2014). In our study we did not find a significant correlation between water table depth and yield (P > 0.30; Fig.…”
Section: Predictability Of Root Growth and Water Table Effectscontrasting
confidence: 54%
“…We attribute this to the timing of the excessively shallow groundwater flooding, which was primarily early in the growing season. Though corn is more sensitive to wet conditions in early vegetative stages of development [ Ahmad and Kanwar , ; Zaidi et al ., ] and flooding stunted growth and killed plants in localized sections of the field leading to wet sensitivity (Figure ), the damage occurred early enough in the growing season that most plants were able to recover and generate full canopies by harvest time. The same regions then had increased water availability due to shallow WTD and less stress during the reproductive period, which is more critical from a yield perspective [ Robins and Domingo , ; NeSmith and Ritchie , ; Çakir , ; Hammad et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Excessive precipitation can inhibit seed germination and emergence, and affect vegetative growth of corn. Flooding can reduce corn height, biomass production [5][6][7], yield [5,8,9], and photosynthetic efficiency by damaging leaf chloroplasts [10]. Excessive rainfall can reduce corn yield by up to 34% compared to the expected yield, which is similar to the 37% reduction observed from extreme drought stress [11].…”
Section: Introductionmentioning
confidence: 69%